Cicero's Catilinarians - Berry, Dominic (Oxford University Press, 2020)
In this discussion of Cicero's 'Catilinarians', D.H. Berry considers how the speeches should be interpreted as literature. Can we treat them as representing what Cicero actually said? Or do we have to read them merely as political pamphlets from a later time?
10.1093/oso/9780195326468.001.0001
Keywords: Cicero; Marcus Tullius; In Catilinam